Science communication in higher education: global perspectives on the teaching of science communication - Roche, Joseph (My University, 2023)
This special issue focuses on the global landscape of teaching science communication in higher education. Following an open call, we selected seven papers with topics including the geographical distribution of science communication programmes, indicators of quality, programme analysis, self-reporting tools, interdisciplinarity, sustainability, and competencies. Collectively, these contributions highlight how the field has grown and increased in complexity, and highlights challenges faced by educators and the significance of addressing them within local and global contexts.
Keywords: Professionalism, professional development and teaching in science communication; Science communication degree programmes; Science communication teaching; SCIENCE COMMUNICATION; Science & Society